Woodcarving Panels in Johor Traditional Malay Houses Influenced by the Islamic Principle - Hanita Yusof; Izudinshah Abd Wahab; Azmal Sabil; Nur Amalina Hanapi (Journal of Islamic Architecture, 2022)
Woodcarving can be influenced by numerous aspects, including religions and beliefs, which may be comprised of the selections of motifs and also wood-carving panels. In Johor, Malay is one of the major ethnic groups and is considered the majority of the state's population, contributing to the significant heritage, including architecture. Traditional Malay houses in Johor have in-stilled woodcarving into some placements of the houses, including windows on jerejak panels. This paper aims to identify the typology of woodcarvings panels and the percentage of usage among the panels found in Johor Malay houses to identify its influence. 72 Johor traditional Malay houses with distinctive woodcarvings were selected to do inventory, photographed, and analyzed. Interviews were conducted while the samples taken were discussed and verified by woodcarving experts. Results show five-piece panels take the highest percentage while six-piece panels come in second in the overall statistic where it is concluded that the Pillars of Islam/Rukun Islam and Pillars of Faith/Rukun Iman have been the influence on the findings. The findings show that the Islamic religion is the most significant influence contributing to the justification of choice. This study can bring recognition to Johor woodcarvings and contribute valuable guides for woodcarvers to apply these panel typologies to their future works to sustain and cherish the Johor houses' wood-carving identity